2000
DOI: 10.1215/15228517-2-4-229
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant primary CNS lymphoma

Abstract: The records and neuro-imaging studies of 8 cases of posttransplant primary CNS lymphoma (PT-PCNSL) diagnosed at Mayo Clinic Rochester between 1970 and 1998 were reviewed retrospectively. All patients received organ transplantation. Patients who had hematologic transplantation were not included in the analysis. The median and mean age of the 4 men and 4 women was 45 years (range, 34 to 50 years). The median duration of symptoms before diagnosis was 36 days (range, 5 to 98 days). At diagnosis, the neurologic exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…In contrast to lesions involved in systemic posttransplant lymphoproliferative disorders, which are heterogeneous and include low-grade proliferations, those arising in the CNS seem to be uniformly high-grade B-cell lymphomas. 7,31 Similar to PCNSLs seen in patients with AIDS, these tumors tend to be multifocal, necrotic, and mostly located in the cerebral cortex and white matter and in the basal ganglia.…”
Section: Posttransplant Pcnslmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to lesions involved in systemic posttransplant lymphoproliferative disorders, which are heterogeneous and include low-grade proliferations, those arising in the CNS seem to be uniformly high-grade B-cell lymphomas. 7,31 Similar to PCNSLs seen in patients with AIDS, these tumors tend to be multifocal, necrotic, and mostly located in the cerebral cortex and white matter and in the basal ganglia.…”
Section: Posttransplant Pcnslmentioning
confidence: 99%
“…21,31 Histologically, PCNSLs in AIDS patients are high-grade, diffuse large B-cell tumors, often of the immunoblastic subtype. The low-grade lymphomas seen occasionally in immunocompetent individuals occur even less frequently in AIDS patients.…”
Section: Patients With Aidsmentioning
confidence: 99%
“…The predominance of the monomorphic type over the polymorphic type (100% vs. 0%) has been reported in CNS PTLD. 5,17) However, another study reported a contradictory result (21% vs. 79%). 20) Both of our cases involved polymorphic PTLD, but classification of PTLD in the Asian population has not been determined.…”
Section: Discussionmentioning
confidence: 98%
“…Most cases obtaining complete remission were treated with other therapeutic modalities, including surgical resection, chemotherapy, and radiotherapy. 5,16,17,20) Chemotherapy such as CHOP (cyclophosphamide, adriamycin, vincristine, and prednisolone) and anti-B-cell antibody have been also used in the treatment of non-CNS PTLD. 9) However, CNS PTLD is considered resistant to these agents, because of the low drug permeability of the bloodbrain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…After a 3-fold rise two decades ago, the incidence of PCNSL continues to increase at a rate of 0.46 per 100,000 patient-years (1,3). The increasing incidence can be partially attributed to prolonged survival of AIDS patients and the extensive use of immunosuppressive therapy in organ transplantation and autoimmune disease (4). However, there has also been a 3-fold increase in the incidence of PCNSL among immunocompetent patients, within some studies representing more than 6% of primary intracerebral neoplasms (5).…”
Section: Introductionmentioning
confidence: 99%